Precarious Academics: Information Practices and Challenges - Willson, Rebekah; Julien, Heidi (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2020)
This paper reports the results of a small-scale study of the information practices of contract academic staff in the United Kingdom, which is being used as the basis for a broader study in the Canadian context. Neoliberal approaches to the management of higher education across the globe, including Canada, are contributing to a highly challenging environment for contract academic staff, who face marginalization, insecurity, and significant stress. The study seeks to give voice to this growing complement of contract academic staff, to identify practical responses to these challenges. Cet article présente les résultats d'une étude à petite échelle des pratiques d'information du personnel universitaire contractuel au Royaume-Uni, qui sert de base à une étude plus large dans le contexte canadien. Les approches néolibérales de la gestion de l'enseignement supérieur à travers le monde, y compris au Canada, contribuent à créer un environnement très difficile pour le personnel académique contractuel, confronté à la marginalisation, à l'insécurité et à un stress important. L'étude cherche à donner la parole à ce complément croissant de personnel académique contractuel, afin d'identifier des réponses pratiques à ces défis.